Are We Prepared to Face the Grey Tsunami? A Review on Laws for the Elders - Thiruchelvam, Jeya Mhiruna; Tahir, Zulazhar (The Malaysian Journal of Social Administration, 2021)
One of the most notable demographic trends worldwide is the growth of the older population, who are aged 65 and above. The world is now going through a phase where the number and the proportion of older persons are increasing. Being an ageing society, the issue of elderly abuse, the welfare and well-being of the elderly population is essential. The problem of abuse and neglect towards the elderly is a subject matter that individuals and communities in our society need to be sensitized. Malaysia will be in the group of ageing nations, with older persons constituting more than 15 per cent of the population by 2030. With the grey tsunami ahead of us, Malaysia must ensure that the laws and policies address the elderly and their welfare issues. Hence, this paper examines the current laws and policies concerning elderly abuse in Malaysia.